The Effect of Locus of Control and Communication Toward Employee Performance - Ahmad Soleh; Rinto Noviantoro; Deky Putrafinaldo (Management and Sustainable Development Journal, 2020)
The purpose of this study was to determine the effect of locus of control and communication toward employee performance in Bank Indonesia representative office of Bengkulu Province. The sampling technique is a census of 48 permanent employees. Data collection using questionnaires and analytical methods used are multiple linear regression, test of determination and hypothesis testing. The results showed that locus of control and communication had a positive and significant effect partially and simultaneously toward employee performance in Bank Indonesia representative office of Bengkulu Province.